A trajetória intelectual de Silvino Olavo: uma análise histórica, cultural e educacional - Batista, Simone Vieira (2011)
The general objective of this research and draw / draw / write biographically intellectual trajectory of Silvino Olavo from 1916 to 1933 in Paraíba - PB, focusing on school and academic formation of this character in investigative effort to emerge from the historically and socially constructed habitus by education to understand who , how , and through which strategies , Silvino Olavo was made and was made intellectual . To do so , use it as theoretical- methodological support the studies of BOURDIEU (2006 , 1974, 1978, 1998) , DOSSE (2009 ) , RODRIGUES (2002 ) , CHARTIER (1990, 1991) , LE GOFF ( 1996, 1998 ) , GADAMER ( 1999) that allowed intrude in this intellectual life through the exegesis of biographies , memoirs of the reports , the journalistic criticism and own journalistic and poetic production olavianas . Thus , to write biographically intellectual trajectory of Silvino - journalist , poet , lawyer, politician , intellectual , melancholy , restless, religious, modern, schizophrenic , a satirical mood and picaresque , obsessed with the lugubrious and ominous side of existence , but at the same time of life , women of science , man of his time , he used the words as a weapon of survival when the beat depression , affective disillusion , despair , loneliness lover allowed me to understand how education builds and strengthens identities and produces effects on individual trajectories of people , constituting a filter through which human beings will subsequently perceive the outside world and base their future choices (BOURDIEU , 2006) . This is the task imposed on those seeking to translate and give unity to all that many some other was ( PIRANDELLO , 2001 ) . If the importance as a lawyer and poet was blatant from the beginning of this research , the importance and intellectual , friend , journalist and son was emerging slowly , appearing as a photo developer . Despite the many traces of sketchy outline , still lacks details . And this report is intended not definitive , exhaustive biography. Before and profile, a picture , a cut of those thousands of faces . So, although there is much to say about Silvino Olavo Martins da Costa . Many files to roll , lots of photos to remind us . Another hundred thousand to be studied. Other than that , can you go enjoying the way , every nuance , detail.